Biological Photothermal Nanodots Based on Self-Assembly of Peptide–Porphyrin Conjugates for Antitumor Therapy - Zou, Qianli; Abbas, Manzar; Zhao, Luyang; Li, Shukun; Shen, Guizhi; Yan, Xuehai (Journal of the American Chemical Society, 2017)
Photothermal agents can harvest light energy and convert it into heat, offering a targeted and remote-controlled way to destroy carcinomatous cells and tissues. Inspired by the biological organization of polypeptides and porphyrins in living systems, here we have developed a supramolecular strategy to fabricate photothermal nanodots through peptide-modulated self-assembly of photoactive porphyrins. The self-assembling nature of porphyrins induces the formation of J-aggregates as substructures of the nanodots, and thus enables the fabrication of nanodots with totally inhibited fluorescence emission and singlet oxygen production, leading to a high light-to-heat conversion efficiency of the nanodots. The peptide moieties not only provide aqueous stability for the nanodots through hydrophilic interactions, but also provide a spatial barrier between porphyrin groups to inhibit the further growth of nanodots through the strong π-stacking interactions. Thermographic imaging reveals that the conversion of light to heat based on the nanodots is efficient in vitro and in vivo, enabling the nanodots to be applied for photothermal acoustic imaging and antitumor therapy. Antitumor therapy results show that these nanodots are highly biocompatible photothermal agents for tumor ablation, demonstrating the feasibility of using bioinspired nanostructures of self-assembling biomaterials for biomedical photoactive applications.